2018
DOI: 10.25165/j.ijabe.20181102.3390
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought stress on photosynthesis and chlorophyll fluorescence images of soybean (Glycine max) seedlings

Abstract: The main purpose of this research is to provide a theoretical foundation for the screening of drought-resistant soybean varieties and to establish an efficient method to detect the PSII actual photochemical quantum yields efficiently. Three soybean varieties were compared in this experiment after 15 d when they were planted in a greenhouse. These varieties were then exposed to light drought stress (LD) and serious drought stress (SD) conditions. With five times' measurement, chlorophyll fluorescence and soil-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 19 publications
5
43
2
Order By: Relevance
“…The strengthening relationship between A n and ChlF ratio has been observed in previous studies (Murchie & Lawson 2013;Su et al 2015). For example, Wang et al (2018) found a significant linear relationship between A n and F v /F m in the soybean experiment under drought conditions. Batra et al (2014) found similar results by studying the ChlF ratio characteristics of mung beans under drought conditions.…”
Section: Drought Stress Strengthens the Relationship Between Net Co 2supporting
confidence: 76%
“…The strengthening relationship between A n and ChlF ratio has been observed in previous studies (Murchie & Lawson 2013;Su et al 2015). For example, Wang et al (2018) found a significant linear relationship between A n and F v /F m in the soybean experiment under drought conditions. Batra et al (2014) found similar results by studying the ChlF ratio characteristics of mung beans under drought conditions.…”
Section: Drought Stress Strengthens the Relationship Between Net Co 2supporting
confidence: 76%
“…Drought stress causes drastic reduction in leaf chlorophyll content, affecting the photosynthetic efficiency of plants, reducing dry matter accumulation and poor grain yield (Wang et al, 2018). In this study, a significant increase (p < 0.05) in plant height, number of branches per plant, number of pods per plant and biomass as well as seed yield with agrochemical application as compared to control was observed.…”
Section: Resultssupporting
confidence: 46%
“…The lack of water could impede the plant growth because water has so many functions for photosynthesis, nutrient and plant assimilates distribution. The decline of photosynthesis in drought-stressed the plant is associated with the stomata restriction (Wang et al 2018) lead to the limitation of carbon assimilation and finally reduce soybean pod production (Stolf et al 2009).…”
Section: Resultsmentioning
confidence: 99%